The introduction and refinement of the assessment of digitally recorded audio presentations. (3rd May 2016) - Sinclair, Stefanie
Abstract: This case study critically evaluates benefits and challenges of a form of assessment included in a final year undergraduate Religious Studies Open University module, which combines a written essay task with a digital audio recording of a short oral presentation. Based on the analysis of student and tutor feedback and sample assignments, this study critically examines how teaching and learning practices linked to this novel form of assessment have been iteratively developed in light of the project findings over a period of two years. It concludes that while this form of assessment poses a number of challenges, it can create valuable opportunities for the development of transferable twenty-first-century graduate employability skills as well as deep, effective learning experiences, particularly – though not exclusively – in distance learning settings.